Evaluation of the surface hardness of composite resins before and after polishing at different times Avaliação da dureza superficial de resinas compostas antes e após o polimento em diferentes tempos - Michelle Alexandra Chinelatti; Daniela Thomazatti Chimello; Renata Pereira Ramos; Regina Guenka Palma-Dibb (University of São Paulo, 2006)
PURPOSE: The aim of this study was to evaluate the surface hardness of six composite resins: Revolution, Natural Flow, Fill Magic Flow, Flow-it! (flowables), Silux Plus (microfilled) and Z100 (minifilled) before and after polishing at different times. MATERIALS AND METHODS: For this purpose, 240 specimens (5mm diameter, 1.4mm high) were prepared. Vickers hardness was determined before and after polishing at different times: immediately, 24h, 7 and 21 days after preparation of the samples. Statistical analysis was performed by ANOVA and Tukey test. RESULTS: There was no difference in the hardness of flowable resins, which had lower hardness than the minifilled resin. The minifilled resin showed the highest surface hardness as compared to the other materials (p<0.01). All materials exhibited higher hardness after polishing, being more evident after 7 days. CONCLUSION: It may be concluded that, regardless of the composite resin, surface hardness was considerably increased when polishing was delayed and performed 1 week after preparation of the samples. PROPOSIÇÃO: O objetivo deste estudo foi avaliar a dureza superficial de seis resinas compostas - Revolution, Natural Flow, Fill Magic Flow, Flow-it! (flowables), Silux Plus (micropartículas) e Z100 (híbrida) - antes e após o polimento realizado em diferentes tempos. MATERIAL E MÉTODO: Foram confeccionados 240 corpos-de-prova circulares (5mm de diâmetro e 1,4mm de altura). A dureza Vickers foi obtida antes e após o polimento realizado em diferentes tempos: imediatamente, 24 horas, 7 dias e 21 dias após a confecção do corpo-de-prova. Os dados foram analisados estatisticamente por meio da ANOVA e do Teste de Tukey. RESULTADOS: Não houve diferença entre as resinas compostas flowable, as quais apresentaram os menores valores de dureza. A resina composta híbrida demonstrou os melhores resultados. Todos os materiais exibiram aumento de dureza após a realização do polimento, que foi mais evidente após 7 dias. CONCLUSÃO: Pôde-se concluir que, independente do tipo de resina composta, a dureza superficial foi consideravelmente maior quando o polimento foi realizado 1 semana após a confecção dos corpos-de-prova.